The effect of pineapple waste (Ananas comosus (L). Merr) subtitution on mixed basal diet of Elephant grass and calliandra on rumen ecosystem of sheep - Y. Widiawati (Jurnal Ilmu Ternak dan Veteriner, 2009)
The aim of this study was to evaluate the effect of pineapple waste substitution to mixed basal diet of Elephant grass and calliandra on rumen ecosystem. Pineapple waste was substituted to basal of Elephant grass and calliandra leaves (3:2) at the level of 0% (RA); 10% (RB); 20% (RC); 30% (RD); 40% (RE) and 50% (RF). In this experiment 24 Indonesian local male sheep (9-10 months old, 15.3 kg average body weight) were used, and were divided into 6 groups of dietary treatment (4 sheep each). Every group was offered one of the experimental diets (RA to RF) in a Completely Randomized Design. Pineapple waste was offered gradually for one month until the level of 50% (RF) was reached. The animals were adapted to experimental diets for about 14 days prior to the data collection period. Rumen fluids from each animal was taken (5 hours after morning feeding) for pH, ammonia concentration; bacteria and protozoa population analysis. The results showed that substitution of pineapple waste up to 30% had no effect on pH, but when the level was increased up to 40 and 50%, the pH (P<0.01) decreased. Ammonia concentration was similar when 10% of the pineapple waste was included, then it decreased significantly when the waste was given up to 50% (P<0.01). A decrease in bacteria population and an increase in protozoa population happened when the waste given was increased up to 50% but it wasn’t significant (P>0.05). Increasing pineapple waste given increased population of amyllolytic bacteria but decreased the population of cellulolytic bacteria. On the Elephant grass and calliandra basal diet with the proportion of 3 : 2, the best substitution of pineapple waste was up to 20%. Key words: Pineapple Waste, Rumen, Bacteria, Protozoa, Ammonia